Influence of ZOE and formocressol on shear bond strength of composite to the dentin of primary teeth - Soleymani AA; Bahrololoomi Z; Parkam S (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Nowadays, removable partial dentures are applied to patients who are not able to use dental implants or fixed prosthesis. Although based on the studies the users of removable partial dentures are in the risk of plaque accumulation and unacceptable changes such as gingivitis, periodontitis and mobility in abutment tooth. It is not clear whether the negative effects of removable partial dentures are more on the isolated teeth which are a kind of abutment adjacent to endentulous area in both sides. The purpose of this study was to investigate the clinical condition of isolated abutment teeth without splinting in comparison to control abutment from the aspects of B.O.P (bleeding on probing), mobility, pocket depth and gingivitis."nMaterials and Methods: In this cross-sectional study, the prepared questionnaires were filled out by 50 patients who received removable partial dentures in department of removable prosthodontics of dental school of Tehran University of Medical Sciences. The patients had isolated abutment tooth and did not have any systemic disease. The obtained data were analyzed. Using Wilcoxon, exact Fisher and Kruskal-Wallis test."nResults: B.O.P (P=0.004), pocket depth (P=0.035), and mobility (P<0.001) in isolated abutments were more than those in control abutments, but there were not significant differences in the degree of caries (P=0.083) and gingivitis (P=0.07)."nConclusion: This study showed that clinical condition of isolated abutments is worse than that of control abutments. More attention should be paid to healthiness of isolated teeth without splinting and periodic follow ups should be done in these cases.